Skeletal muscle dysfunction in chronic obstructive pulmonary disease - Bozkanat Erkan; Jeffery Mador M (Respiratory Research, 2001)
Abstract It has become increasingly recognized that skeletal muscle dysfunction is common in patients with chronic obstructive pulmonary disease (COPD). Muscle strength and endurance are decreased, whereas muscle fatigability is increased. There is a reduced proportion of type I fibers and an increase in type II fibers. Muscle atrophy occurs with a reduction in fiber cross-sectional area. Oxidative enzyme activity is decreased, and measurement of muscle bioenergetics during exercise reveals a reduced aerobic capacity. Deconditioning is probably very important mechanistically. Other mechanisms that may be of varying importance in individual patients include chronic hypercapnia and/or hypoxia, nutritional depletion, steroid usage, and oxidative stress. Potential therapies include exercise training, oxygen supplementation, nutritional repletion, and administration of anabolic hormones.